Peningkatan Kompetensi Pengecoran Logam melalui Pemanfaatan Tungku Berbahan Bakar LPG dan Kowi Berbasis Limbah di SMK Negeri 2 Kudus - Rusiyanto Rusiyanto; Rahmat Doni Widodo; Kaleb Priyanto; Ruben Bayu Kristiawan; Muhammad Zakky Mubarok; Muhammad Emir Al Hakim; Yudistira Rijal Andika; Hibban Pasya Hafid; Julivan Brian Womsiwor (Universitas 45 Surabaya, 2025)
This community service program aimed to improve vocational students’ competence in metal casting by introducing LPG-fueled furnaces and UNNES crucibles fabricated from evaporation boat waste. The partner, SMK Negeri 2 Kudus, faced two main challenges: limited utilization of aluminum scrap from automotive practice and the absence of affordable, durable crucibles for repeated casting activities. The program applied a structured approach consisting of socialization, training, mentoring, and evaluation. Activities included theoretical instruction, pretest–posttest assessment, and hands-on workshops involving furnace operation, crucible utilization, mold preparation, and aluminum casting. Results demonstrated significant improvements: the average pretest score of 4.85 increased to 9.0 in the posttest, reflecting an 85.57% gain in competence. Qualitative observations showed that students developed greater confidence, teamwork, and adherence to safety standards. Beyond competence improvement, the innovation provided a cost-effective and sustainable solution for recycling aluminum scrap and reducing dependence on expensive imported crucibles. The program effectively integrated research-based technology into vocational education and aligned with the Teaching Factory model. This collaboration between university and school can serve as a replicable model for other vocational institutions seeking to strengthen practical skills, sustainability, and industry relevance.